Pemberdayaan bagi Masyarakat Mudah dan Bisa Jadi Usaha Rumahan Melalui Pelatihan Pengembangan Wirausaha Cara Ternak Ikan Cupang Di Kelurahan Putat Jaya Surabaya - J E Sutanto; Tina Melinda; David Sukardi Kodrat (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2020)
The purpose of community empowerment activities is a caring action from the Implementation Team of Ciputra University Surabaya towards the community to increase knowledge and carry out easily with direct practice. These community empowerment activities use lecture methods, group discussions, entrepreneurship training, FGDs, and the practice of operating facilities and infrastructure. First, about the importance of raising betta fish and an easy way to prevent dengue hemorrhagic fever (DHF), so that public health factors become better and the possibility of contracting DHF is relatively slight. Statistical data in the city of Surabaya shows a significant decrease in DHF sufferers. Second, after being given entrepreneurship development training, it is hoped that the community individually can become a home-based business opportunity as well as making it an effort to empower the citizens' economy, bearing in mind that raising betta fish can have additional income for the community. Third, the location factor of Putat Jaya Village is very strategic, so that it becomes a business opportunity for the Putat Jaya community, especially for prospective consumers from inside and outside Surabaya to reach locations to get betta fish more efficiently.